FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PARTISIPASI PETANI PROGRAM PUPM DI PONOROGO - Sri Astuti (Universitas Islam Kadiri, 2020)
This research aims to determine the factors affecting the participation rate of farmers PUPM program, knowing the influence of factors affecting the participation rate of farmers PUPM program. The location of the research was determined intentionally by four Gapoktan in Ponorogo who received the PUPM program in 2016: (1) Duck Pelem, Serangan, Mlarak; (2) Tunas Mulya, Prajekan, Sukorejo; (3) Mulya Tani, Plosojenar, Kauman (4) Sumber, Trisono, Babadan. The sampling method is performed randomly using proportional random sampling with sample count of 100 people. Data analysis uses multiple linear regression with heterokedastisity models. The results of the study showed: (1) Factors affecting the participation rate of farmers in the PUPM program are non-formal levels of education, revenue, activation of members, land area, group management, organizational culture and government roles, (2) on heterocritical models of non-formal education, income, land area, and organizational culture have significant effect on the level of participation of Gapoktan members, while the activity of members, group management, and government's role has no significant effect on the participation rate of Gapoktan members , (3) Factors that affect the low is the non-formal education and income, the activity of the member is sufficient, the area of land is very low, group management, organizational culture and the role of the Government is good, (4) The participation of Gapoktan members of farmers in the planning and utilization of the results is quite sufficient while participation in the implementation is very low and the evaluation is relatively low. Keyword: Gapoktan; Farmer participation; The PUPM